Mengurai Potensi Ekonomi Syariah sebagai Solusi Krisis Keuangan Global: Kajian Mendalam melalui Studi Literatur - Muhammad Syahrul Hidayat (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2023)
This research examines the potential of Islamic economics as a solution in dealing with the global financial crisis through literature studies. In the context of the global financial crisis, Islamic economics offers an interesting alternative approach. The literature study method is used to collect and analyze literature related to Islamic economics and the global financial crisis. The results of the study show that Islamic economics has the potential to overcome the global financial crisis through its principles which prohibit usury, reduce excessive risk, and empower the people's economy. Islamic financial instruments, such as sukuk and profit-sharing financing, also offer a more sustainable alternative. However, the challenges of Islamic financial literacy and regulatory harmonization still need to be overcome. In conclusion, understanding the potential of the Islamic economy can create a stable, inclusive and sustainable financial system in the face of the global financial crisis.